Immersed in Warm Reef Waters - Taylor, Cheryl (LiNQ (Literature in North Queensland), 2016)
Cheryl Taylor reviews; Rosaleen Love, Reefscape. Reflections on the Great Barrier Reef. Allen & Unwin, St Leonards N.S.W., 2000. ISBN 1 86448 873 5.